Imaging findings in patients with axial spondyloarthritis presenting with recurrent fever attacks: data from the international AIDA network spondyloarthritis registry - Di Meglio, Nunzia; Sica, Cristian; Vitale, Antonio; Caggiano, Valeria; Perrella, Armando; Di Martino, Vito; Di Stefano, Margherita; Fratarcangeli, Mauro; Bagnacci, Giulio; Ruscitti, Piero; Cipriani, Paola; Shariat Panahi, Azadeh; et al. (Frontiers in Medicine, 2025)
Spondyloarthritis (SpA) is a group of immuno-mediated diseases likely caused by a complex interaction between autoimmune and autoinflammatory immunological mechanisms, where a febrile clinical presentation can be an early manifestation. This retrospective study aims to assess the prevalence of inflammatory involvement of the sacroiliac joints (SIJs), pelvis, and lumbosacral spine in patients with axial-SpA and recurrent febrile presentation. MR examinations of 57 patients fulfilling the axial-SpA according to ASAS criteria and presenting with febrile symptoms were evaluated, compared to 30 patients with axial-SpA and no febrile symptoms. 20/57 patients in the axial-SpA group with recurrent fevers underwent a US examination of the SIJs. Structural damage and inflammatory alterations of the SIJs were highly prevalent in both groups. In patients with febrile syndrome, bone marrow edema (78.9%) and erosions (85.9%) were the most prevalent findings in the SIJs; SPARCC score was significantly higher in patients with typical axial-SpA onset (BME: 20.1 ± 12.28 vs. 6.15 ± 3.21; erosions: 22.16 ± 8.13 vs. 6.60 ± 3.08; p = 0.01). Among pelvic enthesitis, enthesitis of the pubic symphysis showed a significant difference in prevalence (p < 0.001). Significant differences were found for the prevalence of vertebral body corner sclerosis (p = 0.01), zygapophyseal capsulitis (p = 0.005), and interspinous enthesitis (p = 0.006). No significant correlation was found between ultrasound findings and MR inflammatory changes (p > 0.05). SIJs and spinal inflammatory alterations and pelvis enthesitis were highly prevalent in axial-SpA patients with and without recurrent fever. Enthesitis of the pubic symphysis, vertebral body corner sclerosis, zygapophyseal capsulitis, and interspinous enthesitis showed a significant difference in frequency between axial-SpA patients with and without fever attacks.